Newly synthesized peripherally octa-substituted zinc phthalocyanines carrying halogen terminated phenoxy-phenoxy moiety: comparative photochemical and photophysical features - KIRBAÇ, Erkan (Turk J Chem, 2020)
This study reports the 3 new phthalonitrile derivatives, namely 4, 5 Bis-[4-(4-bromophenoxy) phenoxy] phthalonitrile ( 1 ), 4,5 Bis-[4-(4-chlorophenoxy) phenoxy]phthalonitrile ( 2 ), and 4, 5 Bis[4-(4-fluorophenoxy) phenoxy] phthalonitrile ( 3 ). Their octa-substituted zinc phthalocyanines ( 4 , 5 , 6 ) are reported for the first time in this study. The resulting compounds were characterized by utilizing some spectroscopic methods, such as UV-Vis, 1HNMR, FT-IR spectroscopy, as well as mass spectraand elemental analysis. To show photosynthesizer’s potential, emission (F F ), singlet oxygen (1O2), and photodegradation quantum yields (F∆, Fd) of octa-peripherally phthalocyanines (Pcs) were performed in the solutions, such as biocompatible solvent DMSO (dimethyl sulfoxide) as well as DMF (dimethylformamide) and THF (tetrahydrofuran). Solvent and octa-peripherally binding effect of the halogen (Br, Cl, F) terminated phenoxy-phenoxy groups on phthalocyanine rings for photophysicochemical properties ( 4 , 5 , and 6 ) were compared with the tetra-peripherally and tetra nonperipherally substituted derivatives. The new dyes ( 4 to 6 ) may be evaluated in photodynamic therapy (PDT) of cancer as photosensitizers due to efficient 1O2 from 0.55 to 0.75.